No apparent trade-offs associated with heat tolerance in a reef-building coral - Liam Lachs; Adriana Humanes; Daniel R. Pygas; John C. Bythell; Peter J. Mumby; Renata Ferrari; Will F. Figueira; Elizabeth Beauchamp; Holly K. East; Alasdair J. Edwards; Yimnang Golbuu; Helios M. Martinez; et al. (Communications Biology, 2023)
Abstract As marine species adapt to climate change, their heat tolerance will likely be under strong selection. Yet trade-offs between heat tolerance and other life history traits could compromise natural adaptation or assisted evolution. This is particularly important for ecosystem engineers, such as reef-building corals, which support biodiversity yet are vulnerable to heatwave-induced mass bleaching and mortality. Here, we exposed 70 colonies of the reef-building coral Acropora digitifera to a long-term marine heatwave emulation experiment. We tested for trade-offs between heat tolerance and three traits measured from the colonies in situ – colony growth, fecundity, and symbiont community composition. Despite observing remarkable within-population variability in heat tolerance, all colonies were dominated by Cladocopium C40 symbionts. We found no evidence for trade-offs between heat tolerance and fecundity or growth. Contrary to expectations, positive associations emerged with growth, such that faster-growing colonies tended to bleach and die at higher levels of heat stress. Collectively, our results suggest that these corals exist on an energetic continuum where some high-performing individuals excel across multiple traits. Within populations, trade-offs between heat tolerance and growth or fecundity may not be major barriers to natural adaptation or the success of assisted evolution interventions.